211k views
0 votes
Simplify the expression 5(-7 + 3k)

User Nollidge
by
5.0k points

1 Answer

2 votes

The given expression is,


5(-7+3k)

Opening the brackets and multiplying each term inside the bracket with 5, we get,


\begin{gathered} \lbrack5*(-7)\rbrack+(5*3k)=-35+15\text{ k} \\ 15k=35 \\ k=(35)/(15)=2.33 \end{gathered}

The simplified expression is 15k = 35 and the value of k is 2.33.

User Birdy
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.